Efficacy of Albendazole Against Strongylus sp. and Hematology Changes on Equine in Yogyakarta Special Region - yuriadi yuriadi; Ida Tjahajati; Guntari Titik Mulyani; Kelviano Muqit; Aidah Rahmanita (Jurnal Sain Veteriner, 2021)
The infestation of Strongylus sp. in horses can cause losses to horse breeders, including anorexia, anemia, gastrointestinal diseases and can cause death and decrease the horse population in DIY. Albendazole was a Benzimidazole preparation that is often used to treat worms in ruminants. This study also aims to determine the effect of Albendazole on blood images before and after treatment. The material used in this study were 10 horses with male and female sex,  over 3 years old, and infected with Strongylus sp. with an infestation rate of 200 EPG in faeces. Before treatment of drug was carried out, the faeces was examined with Mc Master method. After treatment with Albendazole, the worm eggs were examined three times at intervals of three days. Routine examination of worm eggs and blood was carried out at the Laboratory of the Department of Internal Medicine, Faculty of Veterinary Medicine, Universitas Gadjah Mada. The results showed that the EPG number decreased from the 0th, 3rd, 6th and 9th day of examinations. The average number of EPG on the 0th day was 990 eggs/gram, and the examination on the 9th day showed the number of eggs was 0 eggs/gram. The results of the hematology examination also showed no significant difference except for the high number of eosinophils on the 12th day after drug administration. The conclusion from this research is that Albendazole as a worm medicine can kill Srongylus sp. however, it does not affect the horse's hematology and health status.